Cybersecurity Challenges In The Era Of Digital Transformation A Comprehensive Analysis Of Information Systems - Adi Ahmad; Riyan Maulana; Muhammad Yassir (STMIK Indonesia Banda Aceh, 2024)
Increased digitalization in business transformation has provided significant benefits, but has also created new challenges for information security. This research aims to analyze the cyber security challenges faced in the era of digital transformation, with a focus on Information Systems. The research method used is a comprehensive analysis of literature and case studies to gain an in-depth understanding of these issues. In this research, we found that there are a number of significant challenges related to cyber security in implementing digital transformation, including malware attacks, phishing, insufficient network security, and privacy violations. Causal analysis concluded that insufficient training and security awareness, as well as weak design in information systems, were the main risk factors. The implication of this research is the need for proactive steps in implementing strong security practices in information systems, including adequate training for employees, careful security monitoring, and early warning of security threats. In addition, the importance of collaboration between organizations, governments and related entities in facing increasingly global threats was also highlighted.